Cover Image, Volume 119, Number 9, September 2022. Issue 9 (13th August 2022) - Koyuturk, Izel; Kedia, Surbhi; Robotham, Anna; Star, Alexandra; Brochu, Denis; Sauvageau, Janelle; Kelly, John; Gilbert, Michel; Durocher, Yves
Abstract : The cover image is based on the Article High‐level production of wild‐type and oxidation‐resistant recombinant alpha‐1‐antitrypsin in glycoengineered CHO cells by Izel Koyuturk et al., https://doi.org/10.1002/bit.28129 . Image Credit: Yves Durocher.